2024
DOI: 10.1371/journal.pgen.1011202
|View full text |Cite
|
Sign up to set email alerts
|

The PP2A-like phosphatase Ppg1 mediates assembly of the Far complex to balance gluconeogenic outputs and enables adaptation to glucose depletion

Shreyas Niphadkar,
Lavanya Karinje,
Sunil Laxman

Abstract: To sustain growth in changing nutrient conditions, cells reorganize outputs of metabolic networks and appropriately reallocate resources. Signaling by reversible protein phosphorylation can control such metabolic adaptations. In contrast to kinases, the functions of phosphatases that enable metabolic adaptation as glucose depletes are poorly studied. Using a Saccharomyces cerevisiae deletion screen, we identified the PP2A-like phosphatase Ppg1 as required for appropriate carbon allocations towards gluconeogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…One notable candidate for the pph22Δ suppressor gene is PPG1, which encodes a serine/threonine type 2Alike protein phosphatase involved in the cell wall integrity pathway [48] that shares 56% identity and 73% protein sequence similarity with Pph22. Studies from S. cerevisiae have shown that Ppg1, and not Pph22, interacts with Far11 to regulate assembly of the Far complex [49,50], which may have pleiotropic roles beyond those of the STRIPAK complex. Our data suggest that an increased dosage of PPG1 may suppress the mutant phenotypes of pph22Δ.…”
Section: Haploid Pph22δ Mutants Exhibit Severe Growth Defects and Fre...mentioning
confidence: 99%
“…One notable candidate for the pph22Δ suppressor gene is PPG1, which encodes a serine/threonine type 2Alike protein phosphatase involved in the cell wall integrity pathway [48] that shares 56% identity and 73% protein sequence similarity with Pph22. Studies from S. cerevisiae have shown that Ppg1, and not Pph22, interacts with Far11 to regulate assembly of the Far complex [49,50], which may have pleiotropic roles beyond those of the STRIPAK complex. Our data suggest that an increased dosage of PPG1 may suppress the mutant phenotypes of pph22Δ.…”
Section: Haploid Pph22δ Mutants Exhibit Severe Growth Defects and Fre...mentioning
confidence: 99%